Educação popular e Educação de Jovens e Adultos: análise dos diálogos em um cursinho popular preparatório para o Exame Nacional do Ensino Médio em Montes Claros - MG - Amanda Imamura Russo (2022)
This study presents an investigation about the presence of graduates of the Brazilian National Program of Youth and Adult Education (EJA) in the pedagogical project of “Podemos Mais” - university entrance exam preparation course - located in Montes Claros, Minas Gerais. In order to analyze the pedagogical project of the popular course Podemos Mais, its relationship with Youth and Adult Education (EJA) and the way in which its teachers see working with students from this teaching modality in their educational activities, it was necessary to characterize EJA as a public policy, and, at the same time, present the definition and characteristics of popular education to build theoretical foundations for data analysis; Identify the characteristics of the education implemented in Montes Claros; Identify the characteristics of EJA graduates who attend the Podemos Mais preparation course; Build the narrative of the history of the Podemos Mais, characterize its pedagogical and political project and identify how it dialogues with popular education; and, finally, to apprehend the perception of the educators of the preparation course Podemos Mais in Montes Claros about the educational actions directed to the EJA students who attend the course and how they interact with these students. In this sense, publications related to the issue were analyzed in three distinct areas: firstly, about the trajectory of Youth and Adult Education and the Popular Education Program in Brazil; secondly about the subjects and characteristics of Youth and Adult Education as a formal education modality; lastly about the performance and practices of the popular university entrance exam preparation course regarding the democratization of access to Higher Education in the country. The methodological choice for the empirical part was based on a simple, qualitative case study, supported by semi-structured interviews and French-based Discourse Analysis with six members of the course, educators, and members of the pedagogical core. Finally, the discourses were confronted with the theory in order to find out how the pedagogical praxis subsidizes an effective participation of the research subjects in the prep course. As a main result, evidence was found that, although the interviewees do not interpret the expressive existence of subjects from EJA, emphasizing the participation of peripheral youth as the main students, the use of Popular Education applied could and can bring benefits to this public. It was concluded that the course has the potential to act in the democratization of access to Higher Education by the subjects of EJA, understanding and acting in the symbolic and institutional violence that this public suffers in their educational and life trajectory, through an emancipatory and critical education that has a political and pedagogical project aligned with their realities.